Development of Wayground Based Educational Games for SKI Instruction in Elementary Madrasah - Andre Fikar Al.Mardhafi; Muhammad Rizqiyanto; Muhamad Aldo Syahputra; Rita Laili Aseh; Melyna Yulianti; Faza Nurul Azmi; Dian Rif'iyati (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
In an effort to increase student enthusiasm and engagement, this study aims to develop a Wayground-based educational game to teach Islamic Cultural History (SKI) in third grade at Madrasah Ibtidaiyah Salafiyah Gapuro. The ADDIE development model, consisting of the analysis, design, development, implementation, and evaluation phases, and a mixed-methods approach, was used in the Research and Development (R&D) methodology of this study. Observations, interviews, and questionnaires were used to collect data, which was then analyzed using descriptive qualitative and quantitative methods. The results indicate that the developed media achieved a student response rate of 90%, classified as “very good,” and attained a very high level of feasibility, as validated by experts, with an average of 89%. These results indicate that students’ enthusiasm for learning, engagement, and understanding of SKI material can be enhanced through the use of Wayground-based instructional game media. Furthermore, compared to conventional approaches, this media can provide a more engaging and participatory learning environment. Therefore, Wayground-based educational game media can serve as a creative alternative for teaching SKI in Madrasah Ibtidaiyah.